2021
DOI: 10.1111/jvs.13045
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐grain beta diversity of Palaearctic grassland vegetation

Abstract: Questions Which environmental factors influence fine‐grain beta diversity of vegetation and do they vary among taxonomic groups? Location Palaearctic biogeographic realm. Methods We extracted 4,654 nested‐plot series with at least four different grain sizes between 0.0001 m² and 1,024 m² from the GrassPlot database, covering a wide range of different grassland and other open habitat types. We derived extensive environmental and structural information for these series. For each series and four taxonomic groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…They were mostly determined in the field, but some additionally retrieved via the plot coordinates (Appendix S1). For simplicity and following a previous paper using the same dataset (Dembicz et al, 2021b), we group them into the following categories, acknowledging that some variables can relate to more than one category: (c) heterogeneity, and (4) vegetation typologies. In the following, we briefly introduce the variables of categories ( 2)-( 4), while details are provided in Appendix S1.…”
Section: Relatingpeakpositiontotaxonomicand Environmental Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were mostly determined in the field, but some additionally retrieved via the plot coordinates (Appendix S1). For simplicity and following a previous paper using the same dataset (Dembicz et al, 2021b), we group them into the following categories, acknowledging that some variables can relate to more than one category: (c) heterogeneity, and (4) vegetation typologies. In the following, we briefly introduce the variables of categories ( 2)-( 4), while details are provided in Appendix S1.…”
Section: Relatingpeakpositiontotaxonomicand Environmental Predictorsmentioning
confidence: 99%
“…If there should be peaks of local z‐values at certain grain sizes this would indicate how spatial heterogeneity of plant communities is organized spatially. As for fine‐grain beta diversity in general (Drakare et al, 2006; Dembicz et al, 2021b) one should also expect peak location of local z ‐values to depend on taxonomic group and various environmental factors. Unfortunately, there are so far no comprehensive macroecological studies to examine the prevalence of peaks in local z ‐values and which drivers determine their position.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the example in Figure5illustrates, the curves only rarely cross each other, meaning that vegetation types mainly differ in their c-values (corresponding to α-diversity), while there are few systematic differences concerning z-values (corresponding to β-diversity). As shown byDembicz et al (2021), z-values are much more affected by disturbance regimes and heterogeneity -which are largely independent of vegetation type.…”
mentioning
confidence: 95%
“…Based on the previous finding that the power function is generally the best approximation of the species–area relationship (SAR) even at very fine grains (10 −4 –10 3 m 2 ; Dengler et al, 2020); two studies used the modelled exponent of the power function ( z ‐value) as a measure of multiplicative beta diversity within nested‐plot series (Dembicz et al, 2021; Zhang et al, 2021). Dembicz et al (2021) found consistent differences in z ‐values between three studied taxonomic groups in relation to elevation and to land‐use intensity and used their findings to propose a new conceptual model for separating causes of fine‐grain beta diversity. Zhang et al (2021) went a step further and asked whether the small deviations from the power law show any regularities.…”
Section: Contributions In the Special Issuementioning
confidence: 99%
“…A total of 15 contributions used fine‐grain plant community data to address macroecological questions at various extents: global (Kusumoto et al, 2021; Testolin et al, 2021), across the whole Palaearctic (Biurrun et al, 2021; Dembicz et al, 2021; Zhang et al, 2021), across Europe (Axmanová et al, 2021; Boonman et al, 2021; Padullés Cubino et al, 2021; Sporbert et al, 2021; Večera et al, 2021), larger parts of Europe (Cao Pinna et al, 2021; Wagner et al, 2021) or at state level (Bourgeois et al, 2021; Craven et al, 2021). Most of these studies rely on two large vegetation‐plot databases established and maintained by two working groups of the International Association for Vegetation Science (IAVS), the European Vegetation Archive (EVA; Chytrý et al, 2016) by the European Vegetation Survey (Axmanová et al, 2021; Boonman et al, 2021; Cao Pinna et al, 2021; Padullés Cubino et al, 2021; Sporbert et al, 2021; Večera et al, 2021; Wagner et al, 2021) and the GrassPlot database (Dengler et al, 2018) by the Eurasian Dry Grassland Group (Biurrun et al, 2021; Dembicz et al, 2021; Zhang et al, 2021). Testolin et al (2021) used data from the global vegetation‐plot database sPlot (Bruelheide et al, 2019), and four relied on regional data compilations (Bourgeois et al, 2021; Craven et al, 2021; Kusumoto et al, 2021; Tordoni et al, 2021).…”
Section: Contributions In the Special Issuementioning
confidence: 99%